Decision making about increased building automation – barriers, drivers and motivation factors - Anna-Lena Lane; Anna-Lena Lane; Andreas Selhammer; Patrik Thollander; Patrik Thollander; Mathias Cehlin (Frontiers in Energy Research)
Energy efficiency has been identified as a way of addressing the need to reduce climate impact from fossil fuels. Furthermore, the ongoing twin transition may provide better and more energy-efficient control of buildings with systems such as building management systems (BMS). However, there appear to be barriers to investments in functional digital tools, as there are for other energy-efficient technologies for buildings. This paper is based on a questionnaire study with technology providers, decision makers and users of building management systems. The questionnaire included questions regarding barriers, drivers, and motivations for investments in BMS. Improved energy efficiency was found to be an important motivation for investments in BMS for users and decision makers, but the technology providers elevated more easy work as important. The main driver for investments in BMS was related to reduced energy costs, while for the decision makers, financial barriers such as risks and hidden cost were ranked highest. An important knowledge barrier was found as knowledge is needed for decisions about investments, use of BMS and decisions regarding IT security, such as handling of data. A key conclusion is the need for a facilitator, as knowledge is needed for decisions about BMS investments and for its use. On a broader scale, the paper argues for the need to include facilitators as a core part of future policies within the twin transition.